Model Latihan Teknik Dasar Lari Sprint MAPHTRAS pada Atlet Lari Pemula - Fahmi, Azwan; Yunus, Moch. (Indonesian Journal of Sport and Physical Education, 2020)
Abstract: Sprint Â is a fundamental technique in athletic sports. The aim of the researcher is to develop 7 models of sprint sprint technique. The research method used is research and development method. Procedure of development (1) needs analysis (2) product planning I (3) product evaluation I (4) product I (5) product trial I (6) product revision I (7) product II (8) trial II product (9) product II (10) product validation and report preparation. The test subjects used were 5 trainees for small group trials, and 10 trainees for large group trials on athlete-age athletes at the Puma Athletic Club of Batu City. The instruments used are questionnaires given to trainees. The results of this research and development are 7 models of sprint sprint training model, 1 "step up run" training model, 2 "3 point start" training model, 3 "hand cycling hamstring" model lattihan, 4 leg cycling hamstring training model, 5 "cycling hamstring" exercise model, 6 "running in palce" exercise model, 7 "jump jump" exercise model. From the research results obtained the data that the exercise model provided to meet the objectives of the research is improving the psychomotor aspect of the training participants to the process of sprint sprint training for beginner athlete at Club PASI Athletics Batu City.Â Keywords: technique training model, sprint run, psychomotor aspect.Â Abstrak: Lari sprint merupakan teknik yang fundamental dalam olahraga atletik. Tujuan peneliti yaitu mengembangkan 7 model latihan teknik lari sprint. Metode penelitian yang digunakan yaitu metode penelitian dan pengembangan. Prosedur pengembangan meliputiÂ  (1) analisis kebutuhan (2) perencanaan produk I (3) evaluasi produk I (4) produk I (5) uji coba produk I (6) revisi produk I (7) produk II (8) uji coba produk II (9) produk II (10) validasi produk dan penyusunan laporan. Subyek uji coba yang digunakan adalah 5 peserta latihan untuk uji coba kelompok kecil, dan 10 peserta latihan untuk uji coba kelompok besar pada atlet usia pemula di Club PASI Puma Atletik Kota Batu. Instrumen yang digunakan berupa kuesioner yang diberikan kepada peserta latihan. Hasil dari penelitian dan pengembangan ini adalah 7 model latihan teknik lari sprint yaitu model latihan 1 â€step up runâ€, model latihan 2 â€œ3 point startâ€, model lattihan 3 â€œhand cycling hamstringâ€, model latihan 4 â€œleg cycling hamstringâ€, model latihan 5 â€œcycling hamstringâ€, model latihan 6 â€œrunning in palceâ€, model latihan 7 â€œbox jumpâ€. Dari hasil penelitian diperoleh data bahwa model latihan yang diberikan dapat memenuhi tujuan dari penelitian yaitu meningkatkan aspek psikomotor peserta latihan terhadap proses latihan teknik lari sprint untuk atlet usia pemula di Club PASI Puma Atletik Kota Batu.Kata kunci: model latihan teknik, lari sprint, aspek psikomotor